Data Mining-Emerging Tool for Market Analysis (Trinity Journal of Management, IT & Media (TJMITM), 2010)
This paper studies data mining as a  nPw and emerging tool for Market  Analysis. Thi:, reveals that Data  Mining which is the process of  extracting various kinds of business  infonnation from the data warehouse  helps in various f unctional areas of  market analysis i.e. Market based  analysis, customer profiling, web marketing ere. to gain the competitive  advantage for the organization. Jr  shows that Data Mining tools perform  market analysis by clearing business  data, enhancing customer knowledge,  enhanced marketing strategies and  increasing profits. This paper reveals how to gain  compe//// ve edge and enhance  business profitability and efficie11cy .  Business organizations worldwide  are taking help of different Data  Mining tools. Data Mining fills the  growing gap between large storage  systems and powerful retrieval  systems and ability to analyze the  information obtained. It helps  contribute to research by providing  association techniques, techniques for  on-line discovery, ensemble learning  and distributed data sets. Large  number of marketing analysis  techniques are related to sales forecasting which can be performed  by the data mining tools. It shows if tools are used by  marketing managers effectively then  it provides an edge to their business.
Keywords: Mining-Emerging Tool; Market Analysis; web marketing